FACTORS INFLUENCING CUSTOMER LOYALTY TOWARD MIXUE ICE CREAM AND TEA SHOP IN JAKARTA - Putra, Jacky Sona; Cokki , Cokki (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to examine the factor influencing customer loyalty directly or indirectly toward customer loyalty through customer satisfaction as a mediating variable. This study's sample size was 200 Mixue ice cream and tea shop customers in Jakarta. The data collection method used in this study is convenience sampling by distributing online questionnaires. The result of this study shows that customer loyalty in Mixue ice cream and tea shops is influenced by product quality, digital marketing, and brand awareness. In addition, the result of this study suggests that companies should focus on the quality of their product and implement digital marketing to increase their loyal customer in line with the digitalization that is happening.